2016
DOI: 10.1007/s40962-016-0115-6
|View full text |Cite
|
Sign up to set email alerts
|

Trace Elements and Graphite Shape Degeneracy in Nodular Graphite Cast Irons

Abstract: Graphite degeneracy in spheroidal graphite cast iron is a common issue faced by foundries. It is generally associated with the presence of so-called poisoning elements and may in some cases be suppressed by the addition of other elements. Mastering these additions is not simple in practice since industrial alloys do generally contain many elements that can affect graphite shape even when present at low or trace levels. In this work, trace and low-level elements are considered in relation with three steps of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 44 publications
(31 reference statements)
2
7
0
Order By: Relevance
“…Based on previous observations [9] and literature review, it has already been pointed out that nuclei may have a rounded shape and be amorphous [6]. In the present study, the rounded nucleus seen in Fig.…”
Section: Discussionsupporting
confidence: 74%
“…Based on previous observations [9] and literature review, it has already been pointed out that nuclei may have a rounded shape and be amorphous [6]. In the present study, the rounded nucleus seen in Fig.…”
Section: Discussionsupporting
confidence: 74%
“…This subject has recently thoroughly and comprehensively been reviewed, for instance, in References 21,22 and 23. In the present article, it is rather a question of treating and consolidating the subject focusing on chunky graphite. In particular, the studies 6,9,13,19,[21][22][23][24][25][26] especially contribute. Although several theories on the formation and growth of chunky graphite in SGI have been proposed, a universal, unanimously accepted explanation has not yet been established.…”
Section: Formation and Growth Of Chunky Graphitementioning
confidence: 99%
“…The used compilation of concentration limits has been elaborated by Reference 44 and complemented in Reference 59. Lacaze 22 concludes the heavier the trace element atoms are, the lower is their critical concentration limit to avoid detrimental influence on graphite shape.…”
Section: Effect Of Chemical Elementsmentioning
confidence: 99%
“…5 In addition, past studies have shown that spheroidization is not only caused by the absence of sulfur, but also that the residual magnesium content in iron supports the formation of graphite spheroids during solidification furthermore. 6 If the required magnesium content is reduced due to external influences, it can lead to degeneration of graphite and therefore to the creation of flake graphite. The most common example of an external influence regarding the casting skin is the binding of magnesium at the interface between the molding material and the melt by sulfur or oxygen.…”
Section: Formation Of the Degenerated Graphite Layermentioning
confidence: 99%